1977
DOI: 10.1002/jgt.3190010208
|View full text |Cite
|
Sign up to set email alerts
|

The biparticity of a graph

Abstract: The biparticity P(G) of a graph G is the minimum number of bipartite graphs required to cover G. It is proved that for any graph G, P ( G ) = {10g2x(G)}. In view of the recent announcement of the Four Color Theorem, it follows that the biparticity of every planar graph is 2.Dedicated to the memory of Paul Turhn BlPARTlClTYThis graphical invariant was defined in [3] along with several other concepts relating to coverings and packings of graphs. The biparticity P(G) is the minimum number of spanning bipartite su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 6 publications
(2 reference statements)
0
32
0
Order By: Relevance
“…Harary [3] has defined the biparticity P(G) of a connected graph G, as the least number of bipartite subgraphs of G which together cover the lines of G. Harary, HSU, and Miller [4] have shown that if x ( G ) is the chromatic number of G, then…”
Section: Introductionmentioning
confidence: 99%
“…Harary [3] has defined the biparticity P(G) of a connected graph G, as the least number of bipartite subgraphs of G which together cover the lines of G. Harary, HSU, and Miller [4] have shown that if x ( G ) is the chromatic number of G, then…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the Singleton bound is a special case of Lemma 6 below with G=+K v . Equality is always attained in Lemma 6 for simple graphs [4].…”
mentioning
confidence: 95%
“…Consequently, if a Hadamard matrix of order 4k exists then bp(2kK 4k ) 4k&1. Equality follows from inequality (4 Deleting the first column of the matrix H above and the 2k rows of H with first entry equal to 1, leaves a 2k by 4k&2 matrix B such that every two rows of B have oppositely signed entries in exactly 2k positions. Thus B is an incidence matrix of a decomposition of 2kK 2k into 4k&2 bicliques.…”
mentioning
confidence: 97%
“…the minimum number of edge-disjoint subgraphs of G that belong to F and cover the edges of G. The parameter is welldefined as long as K2 G F, where Kn denotes the complete graph or clique on n vertices. The parameter Ty(G) has been studied for several families F: F_I rF(G)_ complete graphs clique partition number forests arboricity paths and cycles (see [6]) all bipartite graphs biparticity (see [4]) matchings edge-chromatic number stars vertex cover number…”
Section: Introductionmentioning
confidence: 99%
“…Lovasz's motivation in [6] was the long-standing conjecture of Gallai that every n-vertex graph can be decomposed into [n/2] paths; Lovasz proved that [n/2\ paths and/or cycles will suffice. Harary, Hsu, and Miller [4] proved that for every graph G the minimum number of bipartite graphs that partition its edges is exactly [log2 x(G)], where x(G) denotes the ordinary chromatic number. The edge-chromatic number and vertex cover number (minimum number of vertices needed to have an endpoint of each edge) are well-studied parameters with many applications.…”
Section: Introductionmentioning
confidence: 99%